KINDERGARTEN INFRASTRUCTURE SURVEY IN RURAL AREAS OF BANTUL REGENCY - Hesti Putri Setianingsih (Universitas Tadulako, 2021)
Infrastructure is an important consideration in the aspect of learning, recently there is very little research that examines the condition of infrastructure in Kindergartens. Given the importance of infrastructure in the educational process. The purpose of this study was to determine the condition of infrastructure in the kindergarten in the rural area of ​​Bantul Regency, namely by surveying the condition of the kindergarten infrastructure. This research was conducted in the rural area of ​​Bantul Regency using a cluster random sampling approach, namely Kindergartens throughout Bantul Regency with a total of 100 schools divided into 10 districts, then the school selection used cluster random sampling where 1 (one) school represented 1 (one) sub-district from 10 (ten) subdistricts by drawing a lot for each sub-district, 1 school was taken to be the research sample. The results show that in rural areas Yogyakarta there are 135 availability of infrastructure with category C, namely Moderate and the percentage is 56%.